The last bookaneer [large type] - Pearl, Matthew (Thorndike Press, 2015)
As the 19th century draws to an end, two bookaneers are caught up in a colonial war on Samoa as they compete to steal Robert Louis Stevenson's last manuscript and make a fortune before a new international treaty ends the bookaneers' trade forever.